PI3K and ERK signaling pathways are involved in differentiation of monocytic cells induced by 27-hydroxycholesterol - Son, Yonghae; Kim, Bo-Young; Park, Young Chul; Eo, Seong-Kug; Cho, Hyok-rae; Kim, Koanhoi (The Korean journal of physiology & pharmacology, 2017)
27-Hydroxycholesterol induces differentiation of monocytic cells into mature dendritic cells, mDCs. In the current study we sought to determine roles of the PI3K and the ERK pathways in the 27OHChol-induced differentiation. Up-regulation of mDC-specific markers like CD80, CD83 and CD88 induced by stimulation with 27OHChol was significantly reduced in the presence of LY294002, an inhibitor of PI3K, and U0126, an inhibitor of ERK. Surface expression of MHC class I and II molecules elevated by 27OHChol was decreased to basal levels in the presence of the inhibitors. Treatment with LY294002 or U0126 resulted in recovery of endocytic activity which was reduced by 27OHChol. CD197 expression and cell adherence enhanced by 27OHChol were attenuated in the presence of the inhibitors. Transcription and surface expression of CD molecules involved in atherosclerosis such as CD105, CD137 and CD166 were also significantly decreased by treatment with LY294002 and U0126. These results mean that the PI3K and the ERK signaling pathways are necessary for differentiation of monocytic cells into mDCs and involved in over-expression of atherosclerosis-associated molecules in response to 27OHChol.